In vitro Cell Migration, Invasion, and Adhesion Assays: From Cell Imaging to Data Analysis - Pijuan, Jordi; Barceló, Carla; Moreno, David F.; Maiques, Oscar; Sisó, Pol; Marti, Rosa M.; Macià, Anna; Panosa, Anaïs (Frontiers in Cell and Developmental Biology, 2019)
Cell migration is a key procedure involved in many biological processes including embryological development, tissue formation, immune defense or inflammation and cancer progression. How physical, chemical and molecular aspects can affect cell motility is a challenge to understand migratory cells behavior. In vitro assays are excellent approaches to extrapolate to in vivo situations and study live cells behavior. Here we present four in vitro protocols that describe step-by-step cell migration, invasion and adhesion strategies and their corresponding image data quantification. These current protocols are based on two-dimensional wound healing assays (comparing traditional pipette tip-scratch assay vs. culture insert assay), 2D individual cell-tracking experiments by live cell imaging and three-dimensional spreading and transwell assays. All together, they cover different phenotypes and hallmarks of cell motility and adhesion, providing orthogonal information that can be used either individually or collectively in many different experimental setups. These optimized protocols will facilitate physiological and cellular characterization of these processes, which may be used for fast screening of specific therapeutic cancer drugs for migratory function, novel strategies in cancer diagnosis, and for assaying new molecules involved in adhesion and invasion metastatic properties of cancer cells.